PENGEMBANGAN MEDIA MOBILE LEARNING MENGGUNAKAN FLUTTER PADA MATERI ALJABAR SMP - Kustiawati, Dedek; Sobiruddin, Dindin; Ani, Fauziah Astika Fitri (ALGORITMA: Journal of Mathematics Education, 2025)
The advancement of software technology has led to the emergence of various mobile-based application development platforms such as App Inventor, Android Studio, Xamarin, Thunkable, Flutter, and SDK. However, their potential as media for mathematics learning remains underexplored. This study aims to develop an Android-based mobile learning application using Flutter for teaching algebra in junior high schools. The research employed a Research and Development (R&D) approach, adopting the MOAM (Metodología para Desarrollar Objetos de Aprendizaje Móviles) model, which includes five stages: analysis, design, development, assessment, and publication. Data were collected through observations and interviews, followed by media trials involving 32 seventh-grade students from a selected junior high school in South Tangerang during the 2023–2024 academic year. Expert validation was conducted by mathematics education lecturers from UIN Syarif Hidayatullah Jakarta and junior high school mathematics teachers. The results showed high feasibility, with media and material assessments scoring 95% and 90%, respectively. Feedback from teachers and students also indicated strong approval, with ratings of 96% and 93%. The developed application is considered suitable for supporting algebra learning in junior high schools.   Abstrak Perkembangan teknologi perangkat lunak telah melahirkan berbagai platform pengembangan aplikasi berbasis mobile seperti App Inventor, Android Studio, Xamarin, Thunkable, Flutter, dan SDK. Namun, pemanfaatannya sebagai media pembelajaran matematika masih belum banyak dieksplorasi. Penelitian ini bertujuan mengembangkan aplikasi pembelajaran mobile berbasis Android menggunakan Flutter untuk materi aljabar di tingkat SMP. Metode yang digunakan adalah Research and Development (R&D) dengan model pengembangan MOAM (Metodología para Desarrollar Objetos de Aprendizaje Móviles) yang mencakup lima tahap: analisis, desain, pengembangan, penilaian, dan publikasi. Pengumpulan data dilakukan melalui observasi dan wawancara, serta uji coba media melibatkan 32 siswa kelas VII di salah satu SMP di Tangerang Selatan pada tahun ajaran 2023–2024. Validasi dilakukan oleh dosen Pendidikan Matematika UIN Syarif Hidayatullah Jakarta dan guru matematika SMP. Hasil penelitian menunjukkan bahwa media pembelajaran yang dikembangkan memperoleh penilaian sangat baik, dengan tingkat kelayakan media sebesar 95% dan materi sebesar 90%. Tanggapan guru dan siswa juga positif, masing-masing sebesar 96% dan 93%. Media ini dinyatakan layak digunakan dalam pembelajaran aljabar di SMP.